2019
DOI: 10.1002/jcp.28038
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between microRNAs and Rab family GTPases in human cancers

Abstract: microRNAs (miRNAs), as a group of noncoding RNAs, posttranscriptionally control gene expression by binding to 3′‐untranslated region (3′‐UTR). Ras‐associated binding (Rab) proteins function as molecular switches for regulating vesicular transport, which mainly have oncogenic roles in cancer development and preventing the efficacy of chemotherapies. Increased evidence supported that miRNAs/Rabs interaction have been determined as potential therapeutics for cancer therapy. Nevertheless, instability and cross‐tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 135 publications
(184 reference statements)
0
11
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small (20-23 nucleotides) noncoding RNAs that are conserved evolutionarily [1] Currently, over 28,000 identified mature miRNAs do not encode proteins, but they can regulate gene expression of approximately 30% of biological proteins [2]. These epigenetic molecules regulate the expression of various genes that are involved in critical physiological processes, including differentiation, proliferation, and apoptosis by binding to the 3 -untranslated region region (3'-UTR) of a mRNA molecule [3]. f MiRNAs indicate a new perspective in the study of cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small (20-23 nucleotides) noncoding RNAs that are conserved evolutionarily [1] Currently, over 28,000 identified mature miRNAs do not encode proteins, but they can regulate gene expression of approximately 30% of biological proteins [2]. These epigenetic molecules regulate the expression of various genes that are involved in critical physiological processes, including differentiation, proliferation, and apoptosis by binding to the 3 -untranslated region region (3'-UTR) of a mRNA molecule [3]. f MiRNAs indicate a new perspective in the study of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2020, 21, 2578 2 of 23 of a mRNA molecule [3]. MiRNAs indicate a new perspective in the study of cancers.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that Rab family and the related signalling pathways have been used as therapeutic targets for the treatment of cancers . Increasing evidence has reported that miRNA/Rab interactions play a crucial role in the pathogenesis of cancer, the interaction is considered as potential therapeutics for cancer therapy . Rab10 is one of the multiple Rab isoforms that are implicated in the development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the reduction of some miRNAs was found to be related to higher levels of (Shahabi et al, 2019;Yan et al, 2019). First, to ascertain the miRNAs targeting Rab25, we excavated target genes through two bioinformatics databases (miRDB and Target Scan) and provided a list of miRNAs targeting Rab25.…”
Section: Correlation Between Let-7d and Mir-185 And Rab25 In Bc Tissuesmentioning
confidence: 99%